Poder sobre a vida e potências da vida: práticas de promoção da saúde em instituições religiosas - Roberta Viegas Magalhães (2014)
This study started from the premise that the churches act as potential spaces for the stimulation of healthy lifestyles by promoting an improved quality of life. However, one may question the power relations established in these spaces. The objective of the study was to analyze power relations in health promotion practices in religious institutions. This is a qualitative, exploratory nature with critical post-structuralist approach. The study was conducted within the territory covered Health Center Independence in Barreiro Sanitary District in the city of Belo Horizonte. After mapping the territory, with the identification of religious institutions, were defined for analysis four health promotion practices in which the data were obtained 56 hours of observation and interviews with 25 people between coordinators and participants of practices. Data analysis was supported in the framework of critical discourse analysis. The results indicate a multiplicity of actions and practices developed in religious institutions and called for health promotion. The practices contribute to the formation of a interdiscursivity between biomedicine and religiosity. Access to practices is marked by temporally for healing with the immediate demands that confronts the search for care expressed in the socialization and the bond and promote the possibility of listening, dialogue and strengthening support networks in the daily confrontations. In the social practices, the ordering of life under the guidance of self-care conforms health promotion notions of the analyzed practices. The speeches in this field reveal the process of monitoring the individual established by and about himself, produced by faith in a subjective. We found that health promotion practices operate both in disciplinary control over individual bodies as the regulation on life. Furthermore, the vulnerability of the participants in the previous time the search for practices is transformed into power of life with production of new stories and new ways of savoir-vivre, guided by religion. The power of life responds to power life in a contradictory set of relationships in which the liability to power up by church produces a power that allows the subject to create, produce and varying forms of life by promoting changes in his view and live the world. It is concluded that health promotion practices in religious institutions contribute to the improvement of life. The study provided new insights into the relationships established in the linked practices to religious institutions indicating that they leverage broader ways of intervening in health, considering the subject in its entirety.